Jingle all the way - Schwarzenegger, Arnold; Sinbad, 1956-; Levant, Brian; Hartman, Phil.; Twentieth Century-Fox Film Corporation (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 1997)
A father, deperate to buy a hot-selling Christmas toy, endures a frantic last minute shopping spree on Christmans eve.
Videorecording of the 1996 motion picture.
"This film has been modified from its original version. It has been formatted to fit your screen."--note on container.
Director, Brian Levant ; producers, Chris Columbus, Mark Radcliffe, Michael Barnathan ; executive producer, Richard Vane ; writer, Randy Kornfield ; music, David Newman.
Arnold Schwarzenegger, Sinbad, Phil Hartman, Rita Wilson, Robert Conrad & Jim Belushi.
Rated PG.
VHS format ; Dolby stereo.
Keywords: Films for the hearing impaired; Children's films; Comedy films